Mitochondrial reactive oxygen species scavenging attenuates thrombus formation in a murine model of sickle cell disease. (30th July 2021) - Annarapu, Gowtham K.; Nolfi‐Donegan, Deirdre; Reynolds, Michael; Wang, Yinna; Shiva, Sruti
Abstract: Background: Sickle cell disease (SCD) is characterized by hemolysis‐associated platelet dysfunction that leads to increased risk of thrombosis and plays a role in the high morbidity and mortality of the disease. The mechanisms by which hemolysis induces platelet activation remain unclear. We recently demonstrated that patients with SCD showed increased platelet mitochondrial reactive oxygen species (mtROS) production that correlates with markers of hemolysis and platelet activation. Experiments in isolated platelets demonstrated that mtROS stimulated platelet activation. However, the role of hemolysis‐induced mtROS in thrombus formation in vivo remains unclear. Objectives: Here, we hypothesize that scavenging of mtROS attenuates the propensity for thrombosis in mouse models of hemolysis. Methods: We used models of hemolysate infusion into wildtype mice as well as the Berkley transgenic mouse model of SCD, a chronic mode of hemolysis, to test the effect of hemolysis on platelet mtROS production and thrombosis. Results: We show that infusion of hemolysate in wildtype mice induces platelet mtROS production and decreases time to vessel occlusion in a model of ferric chloride‐induced carotid artery thrombosis. Increased mtROS and propensity for thrombosis was also observed in the Berkley transgenic mouse model of SCD. Notably, treatment with mtROS scavengers decreased platelet mtROS levels and attenuated the propensity for thrombus formation in both models. Conclusions: These data demonstrate that mtROS significantly contribute to the mechanism of hemolysis‐induced thrombosis in vivo and suggest a potential role for mitochondrially targeted antioxidant therapy in hemolysis and SCD‐related thrombosis.